The Role of Elementary School Teachers in Cultivating Students’ Empathetic Character Through Indonesian Folktales - Ilham, M. Adi; Haifaturrahman, Haifaturrahman; Muhdar, Syafruddin (Ahlussunnah: Journal of Islamic Education, 2025)
This article aims to examine the role of elementary school teachers in shaping students’ empathetic character through the use of Indonesian folktales, particularly those originating from West Nusa Tenggara (NTB). West Nusa Tenggara folktales contain diverse moral values that can teach students empathy the ability to understand and share the feelings of others. Using a content analysis approach, this study explores how folktales from Sasak communities in Lombok and Sumbawa can serve as tools for instilling empathy in classroom learning. The findings indicate that folktales enable students to recognize and apply the concept of empathy in their daily lives. Furthermore, the article illustrates how teachers can act as effective facilitators by employing folktales as meaningful and contextually relevant learning media.